Affect, Satisfaction with Life and Pro-Environmental Behavior of Community Gardens Users in Southern Brazil - Chierrito-Arruda, Eduardo; Meira, Bianca Ramos; Menegaldi-Silva, Catherine; Martins, Ana Beatriz Tozzo; Paccola, Edneia Aparecida de Souza; Grossi-Milani, Rute (Fronteira: Journal of Social, Technological and Environmental Science, 2023)
This study aimed to analyze the affect, satisfaction with life and pro-environmental behavior of community garden users. Of the total of participants, 22 (55.5%) were aged over 60 years and 18 (44.5%) were in middle age. Data were obtained through a multi-method methodology. Were applied the Affective Maps Generator Instrument, the Satisfaction with Life Scale, the Positive and Negative Affect Scale and the Environmental Behavior Scale. The results assessed pleasantness, restoration and belonging perception in the community gardens’ environment. High levels of satisfaction with life (M=28.38; SD=5.38) and positive affect (M=40.00; SD=5.51) were obtained. There was a high score in water and energy savings (M=4.14; SD=0.63) as well as in urban cleaning (M=4.62; SD=0.16), and an average score in recycling (M=3.23; SD=0.28) and a low score in activism and consumption (M=2.59; SD=0.14). It is concluded that interdisciplinary strategies should be encouraged to enhance community gardens’ experiences, such as mobile social technologies, which make it possible to encourage emancipatory behaviors among their users.